2003
DOI: 10.1046/j.1462-2920.2003.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community dynamics during start‐up operation of flowerpot‐using fed‐batch reactors for composting of household biowaste

Abstract: Microbial community changes during start-up operation of flowerpot-using fed-batch reactors for composting of household biowaste were studied by quinone profiling, rRNA-targeted fluorescence in situ hybridization (FISH) and cultivation methods. Total and plate counts of bacteria and quinone contents in the reactors increased sharply with time during the start-up period. These increase patterns had two phases; the first increase occurred during 3-4 weeks from the start of waste loading and the second increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 44 publications
6
46
0
Order By: Relevance
“…In this study, we have entirely confirmed our previous observations that a population shift from ubiquinone-containing Proteobacteria to Actinobacteria takes place during the start-up operation of the mesophilic FBC process 12,23,25) . That is, the SCM in the FBC reactors during the early phases of operation contained ubiquinones as the major class of quinone, whereas partially hydrogenated menaquinones became predominant under steady-state conditions.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, we have entirely confirmed our previous observations that a population shift from ubiquinone-containing Proteobacteria to Actinobacteria takes place during the start-up operation of the mesophilic FBC process 12,23,25) . That is, the SCM in the FBC reactors during the early phases of operation contained ubiquinones as the major class of quinone, whereas partially hydrogenated menaquinones became predominant under steady-state conditions.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, bacterial strains isolated previously from FBC systems (strains TUT1003 to TUT1096 and TUT1200 to TUT1296) 12,25) were used. For this test, PBYG agar plates having different levels of aw were prepared by mixing with different concentrations of PEG 300 solution.…”
Section: Growth Tests At Different Levels Of a Wmentioning
confidence: 99%
See 3 more Smart Citations